2002
DOI: 10.1097/00008390-200209000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10, interleukin-6 and interferon-γ gene polymorphisms in melanoma patients

Abstract: The immune response against melanoma can be influenced by cytokines with potentially opposite effects on tumour cell growth, such as interleukin-10 (IL10), interleukin-6 (IL6) and interferon-gamma (IFNgamma). Our objective in this study was to investigate whether polymorphisms in the regulatory regions of IL10, IL6 and IFNgamma genes are associated with the development of primary cutaneous melanoma and/or the prognosis of this tumour. We studied genotypic variations at positions -1082, -819 and -592 in the IL1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 19 publications
3
32
0
1
Order By: Relevance
“…2). Previous studies indicate that IL-10 could be a preferred survival marker, and our results support this fact (Hempel et al, 1997;Martinez-Escribano et al, 2003;Amirzargar et al, 2005).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…2). Previous studies indicate that IL-10 could be a preferred survival marker, and our results support this fact (Hempel et al, 1997;Martinez-Escribano et al, 2003;Amirzargar et al, 2005).…”
Section: Discussionsupporting
confidence: 89%
“…IL-6 is associated with poor prognosis in various malignancies (Deans et al, 2007;DeMichele et al, 2009). Nevertheless, it was reported that this cytokine was not associated with multiple myeloma or primary cutaneous melanoma (Martinez-Escribano et al, 2003;Duch et al, 2007). No data are available on a possible association with CML.…”
Section: Discussionmentioning
confidence: 99%
“…This polymorphism has been implicated in a number of chronic disease conditions including arthritis, coronary heart disease and diabetes (Fishman et al, 1998;Fernandez-Real et al, 2000;Yudkin et al, 2000). In human cancer, the À174 G/C IL-6 polymorphism does not appear to be a risk factor for the development of multiple myeloma or melanoma (Zheng et al, 2000;Martinez-Escribano et al, 2002). Recent data, however, suggest that the C allele is associated with an increased risk of colorectal cancer (Landi et al, 2003).…”
mentioning
confidence: 99%
“…20,32,33 Indeed, this is in line with most other publications regarding IL-10 polymorphisms and melanoma. [22][23][24][26][27][28] In contrast, Nagano et al 34 reported that 'low-expression' IL-10 polymorphisms significantly protected from non-melanoma skin cancer. This may indicate that the effects of IL-10 differ in different skin cancer entities.…”
Section: Methodsmentioning
confidence: 98%
“…Only seven studies investigated the role of proximal IL-10 promoter polymorphisms in melanoma susceptibility and in the course of metastasized melanoma. [22][23][24][25][26][27][28] Martinez-Escribano et al 22 found that the abovementioned proximal IL-10 promoter genotypes (SNPs IL-10 À1087AG , IL-10 À824CT and IL-10 À597AC ) were not associated with melanoma susceptibility. However, IL-10 low-producing haplotypes like ACC/ATA were associated with a shorter survival time and greater tumour thickness.…”
Section: Introductionmentioning
confidence: 99%